POTENTIAL IMPACTS OF CLIMATE CHANGE ON GROUNDWATER RECHARGE AND STREAMFLOW IN A CENTRAL EUROPEAN LOW MOUNTAIN RANGE - Eckhardt K.; Ulbrich U. (My University, 2003)
General Circulation Models simulate significant changes of temperature and precipitation over Europe as part of the anthropogenic climate change. In this study, the impacts of climate change on groundwater recharge and streamflow in a central European low mountain range catchment are investigated using a conceptual eco-hydrologic model, a revised version of the Soil and Water Assessment Tool (SWAT). To improve the reliability of our simulations, we compile plant physiological studies concerning the influence of elevated ambient CO2 concentrations on stomatal conductance and leaf area. Using this information to parameterise the model, we evaluate the impacts of two climate change scenarios, which represent a wide range of assumptions concerning future greenhouse gas emissions and climate sensitivity. The resulting effects on mean annual groundwater recharge and streamflow are small, as increased atmospheric CO2 levels reduce stomatal conductance thus counteracting increasing potential evapotranspiration induced by the temperature rise and decreasing precipitation. There are, however, more pronounced changes associated with the mean annual cycle of groundwater recharge and streamflow. Our results imply that due to the warming a smaller proportion of the winter precipitation will fall as snow. The spring snowmelt peak therefore is reduced while the flood risk in winter will probably increase. In summer, mean monthly groundwater recharge and streamflow are reduced by up to 50% potentially leading to problems concerning water quality, groundwater withdrawals and hydropower generation.
Keywords: CLIMATE CHANGE; GROUNDWATER RECHARGE; STREAMFLOW; STOMATAL CONDUCTANCE; LEAF AREA